On the importance of telemetric temperature sensor location during intraperitoneal implantation in rats. (April 2014) - Chapon, PA; Bulla, J; Gauthier, A; Moussay, S
This study aims to assess the thermal homogeneity of the intraperitoneal (IP) cavity and the relevance of using a fixed telemetric temperature sensor at a given location in studying rodents. Ten rats were intraperitoneally implanted with three Jonah® capsules each; after assessing the accuracy and reliability of the sensors. Two capsules were attached, one to the right iliac fossa (RIF) and the other to the left hypochondrium (LH), and another was placed between the intestines but not attached (Free). In the ex vivo condition, the differences between sensors and reference values remained in the range of ±0.1℃. In the in vivo condition, each sensor enabled the observation of temperature patterns. However, sensor location affected mean and median temperature values while the rats were moving freely. Indeed, temperature data collected in the LH were 0.1℃ significantly higher than those collected in the RIF and temperature data collected in the LH were 0.11℃ significantly higher than those collected with the Free capsules. In in vivo conditions, intra-sensor variability of temperature data was not affected by sensor location. Taking into account sensor accuracy, similar intra-sensor variability, and mean differences observed between the three locations, the impact of sensor location within the IP cavity could be considered negligible. In in vivo conditions, temperature differences between locations regularly exceeded ±0.2℃ and reached up to 2.5℃. These extreme values could be explained by behavioral factors such as food or water intake. Finally, considering the good thermal homogeneity of the IP cavity and possible adverse consequences of sensor attachment, it seems better to let sensors range free within the cavity.